Ulnar Shortening Osteotomy by Chun and Palmer Technique in a case of Ulnar Impaction Syndrome - Rishabh Dubey; Clevio Desouza (Journal of Orthopaedic Reports, 2024)
Background: Ulnar-sided wrist pain frequently emerges as a source of upper extremity impairment. Ulnar impaction syndrome gives rise to a range of conditions affecting the triangular fibrocartilage complex (TFCC) along with associated injuries to the lunate, triquetrum, and ligaments. Patients often present with gradual, insidious ulnar-sided wrist discomfort, accompanied by occasional clicking sensations. A noteworthy portion of these cases traces back to histories of trauma or the repetitive application of axial loading and rotational forces to the wrist. Case presentation: We present to you a case report of a 21-year old male with ulnar impaction syndrome treated with ulnar shortening osteotomy by the Chun and Palmer technique. Conclusions: Ulnar shortening osteotomy by the Chun and Palmer technique is an effective procedure for ulnar impaction syndrome.